EVALUASI KINERJA SIMPANG EMPAT TAK BERSINYAL PADA RUAS JALAN SUNAN KALIJAGA KELURAHAN MERJOSARI KECAMATAN LOWOKWARU KOTA MALANG - Dos Reis, Julio Octavio; Pandulu, Galih Damar (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
Intersection is an integral part of all road systems. The city of Malang has one intersection that has a high density level, namely the intersection of four without a signal located on the road of Sunan Kalijaga, Merjosari Village, Lowokwaru District, Malang City. Therefore there is a need for research to overcome the problems that occur. The purpose of this research is to find the best alternative to solve the problem of vehicle density at intersection Jln. Merto Joyo Selatan - Jln. Joyo Suko Timur - Jln. Simpang Gajayana - Jln. Sunan Kalijaga in Merjosari Village, Lowokwaru District, Malang City for the next 5 years. This study uses primary data and secondary data. Primary data is obtained by an average daily traffic volume survey for 2 weeks at 06:00 - 22:00 WIB, and direct geometric intersection measurements. Secondary data in the form of Malang City population growth data in 2017 and Malang City traffic vehicle growth data. Data analysis in this study was based on MKJI 1997 with the help of MS. Excel 2007. The results of this study indicate that the peak hours in the first week occur on Monday at 16: 00-17: 00 WIB with a traffic volume (Q) of 1683.95 pcu / hour, capacity (C) of 1359,288 junior high school / hour and second week on Wednesday hours 17: 00-18: 00 WIB with a traffic volume (Q) of 1891.55 pcu / hour, capacity (C) of 1359.288 pcu / hour. This shows that the intersection has a level of road service class F (very, very low) so that proper evaluation and handling is necessary. Based on the results of the test analysis, the best alternative for solving these problems is by installing traffic signs prohibited parking, improving alignment or intersection of fields on the road.